2020
DOI: 10.1111/pace.13862
|View full text |Cite
|
Sign up to set email alerts
|

Cavotricuspid isthmus is constantly a zone of slow conduction: Data from ultra‐high‐resolution mapping

Abstract: Background Whether cavotricuspid isthmus (CTI) is a region of conduction slowing during typical flutter has been discussed with conflicting results in the literature. We aimed to evaluate conduction velocity (CV) along the different portions of the typical flutter circuit with a recently proposed method by means of ultra‐high‐resolution (UHR) mapping. Methods Consecutive patients referred for typical atrial flutter (AFL) ablation underwent UHR mapping (Rhythmia, Boston Scientific). CVs were measured in the CTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The same study found that CV in the CTI was significantly slower than that in the septum (p < .05). 31 More recently, Bun's use of ultra-HD mapping confirmed that CTI CVs were constantly twofold slower than atrial conduction velocities outside the CI, 32 which agrees with our results despite some differences concerning the slowdown location inside the CTI.…”
Section: Cti Conduction-velocity Alterationssupporting
confidence: 89%
“…The same study found that CV in the CTI was significantly slower than that in the septum (p < .05). 31 More recently, Bun's use of ultra-HD mapping confirmed that CTI CVs were constantly twofold slower than atrial conduction velocities outside the CI, 32 which agrees with our results despite some differences concerning the slowdown location inside the CTI.…”
Section: Cti Conduction-velocity Alterationssupporting
confidence: 89%
“…In this study, slow conduction was observed near the 1 o'clock position of the tricuspid annulus in all cases with the exception of Patient 8. Previous report demonstrated CTI was a zone of slow conduction in AFL patients without prior cardiac surgery 10 . In nine of the 10 cases in this study, the slow conduction around the tricuspid annulus in STA‐AT were observed at the 1 o'clock of the tricuspid annulus, not CTI.…”
Section: Discussionmentioning
confidence: 43%
“…Previous report demonstrated CTI was a zone of slow conduction in AFL patients without prior cardiac surgery. 10 In nine of the 10 cases in this study, the slow conduction around the tricuspid annulus in STA-AT were observed at the 1 o'clock of the tricuspid annulus, not CTI. Therefore, it was considered that the mechanism of peri-tricuspid STA-ATs would be different from that of typical AFLs without prior cardiac surgery.…”
Section: Effects Of Septal Incision Line Characteristics On the Tachy...mentioning
confidence: 56%
“…The relatively limited number of patients included in this multicenter prospective study can be explained by the additional cost associated with the use of UHD mapping system compared to the standard approach, which limited inclusions of patients. For this reason, studies using UHD for CTI-dependent flutter usually include small populations [ 22 , 23 , 24 ]. Furthermore, activation mapping is more time-consuming (mean acquisition time 6.8 ± 5 min per map), in comparison with differential site pacing technique.…”
Section: Discussionmentioning
confidence: 99%